The Relationship Between General Ethical Judgments and Copying Behavior at Work - Suter, Tracy A. (Journal of business ethics, 2004)
Electronic technologies, in general, and computer-oriented technologies specifically have had a tremendous impact on all aspects of business. One area of increased concern is the protection of intellectual properties -- notably copyrights -- within the boundaries of the broadly defined technology industry. While the ability to share copyrighted information has always existed at the most basic levels, the advent of the information age has allowed the sharing of this information to take place in potentially greater quantities and without a loss of quality. As such, copying creates a major threat to industries dealing in the production and distribution of copyrightable creations. The focus of this paper is to better understand how the ethical judgments of employees regarding the opportunities to recreate copyrighted works via traditional and newer technologies impact assessments of copying behavior in the workplace.